Intellectual capital and organisational performance: The textile industry in Pakistan / Waseem Barkat - Waseem, Barkat (2018)

(untitled)
Intellectual capital (IC) has been argued as one of the key elements for organisation value creation, and has brought drastic productive change in competitive business environment. IC is used in organisation to gain benefits from intangible resources. This concept is well-utilised in developed world and implemented in various manufacturing and service organisations. However, little attention is paid to IC and still empirically under-researched in developing countries especially in Pakistan. This study focuses on the role of IC on organisational performance in textile industry in Pakistan. Further, this study also investigated the individual dimensional effect of IC on organisational performance. In seeking empirical evidences of IC and its dimensions, an interactive and comprehensive model is developed. This study model is based on previous theories and theoretical models. IC as overall and its dimensions: human capital, structural capital, relational capital, and technological capital are applied as independent variable. In investigating the relationship between IC (its dimensions) and organisational performance, organisational performance is measured with management’s perception on internal sales, export growth, and profitability, output per worker, value added per worker, cost of production and new product development. Besides, this research model also utilised the mediating role of knowledge process capability and innovation capability between IC and organisational performance. Knowledge process capability is the combination of knowledge acquisition, knowledge documentation, knowledge creation, and knowledge transfer and knowledge application while innovation capability is composed on product innovation and process innovation. The target population of current study is large textile companies. However, there are no authentic sources which could indicate all large textile companies in Pakistan. Therefore, various sources are utilized to make a complete list of large textile companies. A written survey questionnaire is used for collecting primary data. Simple random sampling is used for collecting the samples. A total of 354 usable questionnaires are collected from 240 companies. The structural equation modelling (SEM) method is applied to estimate the model. The core findings of this study showed that IC has a significance influence on organisational performance. Similarly, all dimensions of IC have significant positive effect on organisational performance except structural capital. Further, knowledge process capability and innovation capability are also found to mediate the relationship between IC and organisational performance. In addition, the mediating role of knowledge process capability with dimensions of IC reveals that all dimensions are found to be significant. Finally, innovation capability is found to mediate with only two dimensions of IC (human capital and relational capital) and organisational performance. This study contributes to the existing body of knowledge by utilising various dimensions of IC and its impact on organisational performance that is under-researched in Pakistan as a developing country. Further, this study has imperative implications in understanding the utilisation of IC in manufacturing and service industries of developing countries. Finally, this study also found constructive suggestions for researchers, top management, decision makers, and the policy makers to improve the likelihood of adopting IC in their respective organisations.